Evaluation of the most intense high-intensity running period in english FA Premier League soccer matches - Di Mascio, M.; Bradley, P. S. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the most intense period of high-intensity running during elite soccer matches. Elite players (n = 100) were analyzed using a multicamera computerized tracking system. High-intensity running (speed >19.8 km·h-1) in 5-min periods were quantified during matches. High-intensity running was performed for approximately 3% of total time, but this doubled (F[1,99] = 9.179, p < 0.001, d > 1.2) during the most intense period (8.4 ± 2.7 vs. 16.4 ± 4.6 seconds). Recovery time between high-intensity efforts was approximately 30 seconds during the most intense period (33.3 ± 19.7 seconds). The work:rest ratio between high-intensity bouts increased (F[1,99] = 2.018, p < 0.001, d > 0.6) from 1:12 for the match average to 1:2 during the most intense period. The distance of each discrete high-intensity running bout increased (F[1,99] = 1.958, p < 0.001, d > 0.6) approximately 13% during the most intense period compared with that of the match average (6.7 ± 1.8 vs. 5.8 ± 0.6 m). Central defenders were running at high-intensity for less (F[4,95] = 4.907, p < 0.05, d > 0.6) time than full-backs, wide midfielders, and attackers (12.9 ± 2.4 vs. 17.9 ± 3.4, 18.3 ± 5.5, and 16.9 ± 3.8 seconds). Central defenders had a greater recovery time (F[4,95] = 3.083, p < 0.05, d > 0.6) between high-intensity efforts than wide midfielders. No differences were evident between playing positions for maximum running speed and average distances of high-intensity running. These results show that high-intensity running, work:rest ratios, and average high-intensity distances change markedly during the most intense period of matches and are highly dependent on positional role. Therefore, conditioning drills and performance tests should closely mimic distances, work:rest ratios, and recovery times of those found during the most intense period of matches.